Comparison Between Decitabine and Azacitidine for Patients With Acute Myeloid Leukemia and Higher-Risk Myelodysplastic Syndrome: A Systematic Review and Network Meta-Analysis - Ma, Jiale; Ge, Zheng (Frontiers in Pharmacology, 2021)
Background: The hypomethylating agents (HMAs) azacitidine (AZA) and decitabine (DAC) have been widely used in patients with acute myeloid leukemia (AML) and higher-risk myelodysplastic syndrome (HR-MDS). However, few direct clinical trials have been carried out to compare the efficacy and adverse events (AEs) between these two agents. The clinical choice between them is controversial. A systematic review and network meta-analysis (NMA) were performed to compare the efficacy, safety and survival of DAC and AZA in AML and HR-MDS patients. Methods: We systematically searched Medline, Embase, Web of Science, and Cochrane Library through March 15, 2021. Randomized controlled trials on AML or HR-MDS patients comparing the efficacy and safety between DAC and AZA, or comparing one of HMAs to conventional care regimens (CCR) were selected. Results: Eight RCTs (n=2184) were identified in the NMA. Four trials compared AZA to CCR, and four compared DAC to CCR. Direct comparisons indicated that compared to CCR, both AZA and DAC were associated with higher overall response(OR) rate (AZA vs. CCR: RR=1.48, 95% CI 1.05-2.1, DAC vs. CCR: RR=2.14, 95% CI 1.21-3.79)and longer overall survival(OS) (AZA vs. CCR: HR=0.64, 95% CI 0.50-0.82, DAC vs. CCR: HR=0.84, 95% CI 0.72-0.98), and AZA showed higher rate of CRi (HR=2.52, 95% CI 1.27-5). For the indirect method, DAC showed higher CR rate than AZA both in patients with AML (RR=2.28, 95% CI 1.12-4.65) and MDS (RR=7.57, 95% CI 1.26-45.54). Additionally, DAC significantly increased the risk of 3/4 grade anemia (RR=1.61, 95% CI: 1.03–2.51), febrile neutropenia (RR = 4.03, 95% CI: 1.41–11.52) and leukopenia (RR=3.43, 95% CI 1.64-7.16) compared with AZA. No statistical significance was found for the other studied outcomes. Conclusion: Compared to CCR, both AZA and DAC can promote outcomes in patients with AML and HR-MDS. DAC showed higher efficacy than AZA (low-certainty evidence), especially in patients with AML, while AZA experienced lower frequent grade 3/4 cytopenia than patients receiving DAC treatment.